A study of optimal assignment with different workers' capacities for each process in a reset limited-cycle problem with multiple periods. (11th January 2022) - Zhang, Jinyu; Yamamoto, Hisashi; Sun, Jing; Kajihara, Yasuhiro
In production activities, the result and efficiency of a certain period of a production cycle are influenced not only by the risks that exist in the current period, but also by the risks that existed in the previous ones. So we constructed a model called a reset limited-cycled model with multiple periods to assume evaluation of the impact risk. Because of the variability of the capacities of workers, the processing time is different among workers. In this paper, we focus on the fact that workers have different processing capacities for different processes under the reset limited-cycled model with multiple periods. Based on that assumption, we propose a new formulation of the expected risk (cost). Furthermore, some theorems of the rule of the optimal worker assignment that minimises the total risk, when there are two types of workers' capacities for each process, are proposed.